Do non-reporting companies in Malaysia engage in social and environmental activities? - Che Adam, Noriah; Phua, Lian; Md. Taib, Fauziah (Taylor & Francis Group, 2014)
This study examines the engagement of social and environmental activities by Malaysian public listed companies that do not present this information in their annual report.This study analyses the contents of annual reports and mailed questionnaire survey to non-reporting companiese.This study provides evidence that although most of Malaysia companies do not report social and environmental information in their annual report however they did engage in certain social and environmental activities.This study provides inputs that Malaysian companies are not interested in voluntarily reporting additional information unless they are mandated through specific laws and regulation.